INNOVATION FORMS OF TOURISM DEVELOPMENT IN PERM REGION - Karpovich, Yu.V.; Lepikhina, T.L. (Perm Federal Research Centre Journal, 2016)
The article describes the innovative tourism forms as one of the priority directions in Perm region development. It examines the positive influence of agri-tourism on the development of the regional economy, characterized by preconditions of agro-tourism development in Perm region.